Does occupational lifting and carrying among female health care workers contribute to an escalation of pain‐day frequency?. (28th May 2012) - Holtermann, A.; Clausen, T.; Aust, B.; Mortensen, O.S.; Andersen, L.L.
Abstract Background The aim of the study was to investigate if different frequencies, loads and trunk postures of occupational lifting and carrying increases the risk of sub‐chronic (1–30 days last 12 months) low back pain (LBP) to become persistent (>30 days last 12 months) among female health care workers. Methods Female health care workers answered a questionnaire about occupational lifting or carrying frequency (rarely, occasionally and frequently), load (low: 1–7 kg, moderate: 8–30 kg and heavy: >30 kg) and trunk posture (upright or forward bent back), and days with LBP in 2005 and 2006. Results The odds ratio (OR) for developing persistent LBP in 2006 from these characteristics of occupational lifting and carrying was investigated with multi‐adjusted logistic regressions among female health care workers with sub‐chronic LBP (n = 2381) in 2005. Among health care workers with sub‐chronic LBP, increased risk of persistent LBP was found from frequently lifting or carrying with forward bent back of moderate loads (OR: 1.63; 95% CI: 1.15–2.33) and heavy loads (OR: 1.56; 95% CI: 1.04–2.34). No increased risk for LBP to develop into a persistent condition was found for frequent lifting with upright back, frequent lifting or carrying of light loads, or occasionally lifting or carrying of any loads. Conclusions Preventive initiatives for sub‐chronic LBP to develop into a persistent condition ought to focus on reducing frequent lifting and carrying of moderate and heavy loads with forward bent back.